Implementasi Konsep Efisiensi pada Redesain Rumah Bahasa Surabaya - Erlina Kurnia Chandra; Lintu Tulistyantoro; Hendy Mulyono (Intra, 2019)
There are still a lot of education spaces in Surabaya, especially foreign language education spaces that have not designed their facilities and learning systems by the needs of its users which has caused the learning systems to be less effective and efficient. Moreover, students are now dominated by generation Z who have different characteristics from the previous generation (millennial). Rumah Bahasa Surabaya which provides learning facilities of 13 foreign languages and 2 local languages, established by the Government of Surabaya, can be developed into a place that is effectively able to provide learning type which will suit the character of generation Z. In order to accomplish it, this project has applied ‘efficiency’ as a design concept. This concept itself has been applied by interior system (especially through lighting system) and users’ circulation arrangement which achieved through the design pattern of the wall and the floor. This design aims to make Rumah Bahasa Surabaya as one of the design requirements for other learning spaces, about designing based on the need of users and an effective yet efficient energy usage (lighting systems, air conditioning, user circulation).